2004
DOI: 10.1002/cncr.20032
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of atypical neurocytomas

Abstract: BACKGROUND The majority of central neurocytomas are benign. Approximately 25% of these rare central nervous system tumors are more aggressive, with an MIB‐1 labeling index > 2% or atypical histologic features, and are classified as atypical neurocytomas. The objective of this analysis was to define the optimal treatment for patients with these atypical tumors. METHODS The first atypical neurocytoma was described in 1989. The patients reported since then were reviewed for age, gender, extent of resection, MIB‐1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 33 publications
(32 reference statements)
0
63
1
1
Order By: Relevance
“…Nevertheless, atypical histological features or centrally located atypical neurocytomas with high-grade mitotic activity are associated with high recurrence rates and unfavorable prognosis. [11,12] Whereas typical features of extraventricular neurocytomas are similar, they have obviously worse prognosis that requires adjuvant therapies. [13,14] Primary treatment of neurocytoma is total surgical excision if possible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, atypical histological features or centrally located atypical neurocytomas with high-grade mitotic activity are associated with high recurrence rates and unfavorable prognosis. [11,12] Whereas typical features of extraventricular neurocytomas are similar, they have obviously worse prognosis that requires adjuvant therapies. [13,14] Primary treatment of neurocytoma is total surgical excision if possible.…”
Section: Resultsmentioning
confidence: 99%
“…Central neurocytoma patient in the present series with MIB-1 labeling index of <2% who underwent STR surgery was irradiated with a dose of 60 Gy/30fr and was still alive after 60 months without any signs of recurrence. Rades et al [12] found that 3-and 5-year local control rates in patients with atypical central neurocytoma were 73% and 57% in total resection group (n=15), and 60% and 31% in STR group. In the present series, the local control rate was 75%.…”
Section: Discussionmentioning
confidence: 99%
“…EVNs are rare, and their clinical characteristics still need to be evaluated. The radiological findings of EVNs mimic gliomas and are effectively treated with complete resection, regardless of histological grade [6,7]. When EVNs display atypical histological features such as vascular proliferation, necrosis, increased mitotic activity and an increased proliferation index, they are classified as atypical EVNs [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…The limited number of EVNs and the heterogeneous radiological findings make the diagnosis of these tumors difficult prior to surgery, and glioma is the most common radiological tentative preoperative diagnosis. The degree of resection, however, is very important for patient prognosis in both classic and atypical EVNs [6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…One of our patients, a 30-year-old man with subtotally resected CN, presents an example of a favorable response to GKRS after a follow-up period of 36 months, though the pathological examination revealed anaplastic features and a high MIB-1 labeling index of 7%. Rades et al [34] studied 85 patients from published reports with tumors that were identified as atypical neurocytomas on the basis of an MIB-1 labeling index of 1 2%. Recently published reports showed that an elevated MIB-1 labeling index of 1 2% is predictive of tumor recurrence and an atypical appearance [35,36] .…”
Section: Atypical Cn and Tumor Recurrencementioning
confidence: 99%